Mammalian TIMELESS Is Involved in Period Determination and DNA Damage-Dependent Phase Advancing of the Circadian Clock - Engelen, Erik (Public Library of Science, 2013)
The transcription/translation feedback loop-based molecular oscillator underlying the generation of circadian gene expression is preserved in almost all organisms. Interestingly, the animal circadian clock proteins CRYPTOCHROME (CRY), PERIOD (PER) and TIMELESS (TIM) are strongly conserved at the amino acid level through evolution. Within this evolutionary frame, TIM represents a fascinating puzzle. While Drosophila contains two paralogs, dTIM and dTIM2, acting in clock/photoreception and chromosome integrity/photoreception respectively, mammals contain only one TIM homolog. Whereas TIM has been shown to regulate replication termination and cell cycle progression, its functional link to the circadian clock is under debate. Here we show that RNAi-mediated knockdown of TIM in NIH3T3 and U2OS cells shortens the period by 1 hour and diminishes DNA damage-dependent phase advancing. Furthermore, we reveal that the N-terminus of TIM is sufficient for interaction with CRY1 and CHK1 as well for homodimerization, and the C-terminus is necessary for nuclear localization. Interestingly, the long TIM isoform (l-TIM), but not the short (s-TIM), interacts with CRY1 and both proteins can reciprocally regulate their nuclear translocation in transiently transfected COS7 cells. Finally, we demonstrate that co-expression of PER2 abolishes the formation of the TIM/CRY1 complex through affinity binding competition to the C-terminal tail of CRY1. Notably, the presence of the latter protein region evolutionarily and structurally distinguishes mammalian from insect CRYs. We propose that the dynamic interaction between these three proteins could represent a post-translational aspect of the mammalian circadian clock that is important for its pace and adaption to external stimuli, such as DNA damage and/or light.